Analisis Kontribusi Sektor Priwisata Terhadap Pendapatan Asli Daerah Kota Batu Periode Tahun 2011-2015 - Indah Puspitasari; Moh. Saleh; Duwi Yunitasari (UPT Penerbitan Universitas Jember, 2018)
The main goal of this research is to determine the development of tourism revenue and the contribution of tourism sector to local revenue (LR) in Batu City. This research use secondary data on the development of tourism revenue and the contribution of tourism revenue to LR in Batu City. This research was conducted using contribution analysis and trend analysis, that development of tourism revenue increased during the period 2011 - 2015. Based of this research showed that the number of tourist arrivals has fluctuated. Based on the result of research analyzes the obtained result that the decrease in the contribution of the tourism sekctor resulting from the increase in tourism revenue are low by the amount of LR from other sectors with a larger amount.Keywords: Tourism sector, local revenue